HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Optimization of Water-saving Performance under Green Finance: a Multi-perspective Game-theoretic Approach - Jie Zhang; Ruolan Sun; Yufei Hu (Water Resources Management, 2026)

Downscaling prediction of urban wind environment based on PBMs and hybrid MLP-CNN model - Xiaohan Shen; Ruolan Sun; Gerui Sui; Rongmao Xu; Xin Zhou; Da Yan; Jingjing An (Urban Climate, 2026)

Comprehensive single-cell profiling uncovers TsMHC-II expression predicting response to neoadjuvant immunotherapy in gastric cancer - Zhiyuan Xu; Zhichun Tang; Simeng Hu; Litao Yang; Jingli Xu; Pengfei Yu; Yian Du; Yanqiang Zhang; Jiahui Chen; Xiaoxiao Wu; Siwei Pan; ShengJie Zhang; et al. (Science Bulletin, 2026)

Al-doped Ti4O7 with superior oxidation resistance and optical stability for high-temperature solar-thermal applications - Peize Lyu; Wenzhao Sun; Bo Yang; Wanqi Chen; Ruolan Tang; Haile Yan; Zongbin Li; Song Li; Liang Zuo (Chemical Engineering Journal, 2026)

Mechanistic differences in ce-MoS2 catalytic activation of peroxides: Pathway divergence and reactive species roles - Shuyun Tai; Lei Sun; Yuxin Wang; Ruolan Huang; Yang Yang; Yu Chen; Hong Chang (Journal of Hazardous Materials, 2025)

Functional differentiation of Sojae semen Praeparatum: A multi-omics analysis of the effects of Artemisia annua and Mori folium on composition, microorganisms, and functional characteristics - Yingying Cheng; Bing Wang; Qiaoling Ma; Min Sun; Xintong Wang; Ruolan Wang; Hongping Chen; Lin Chen; Youping Liu; Fu Wang; Chuan Zheng; Yuan Hu (Food Research International, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

Nanozyme-mediated drug ion-exchange strategy ameliorates inflammatory bowel disease by scavenging ROS and reprogramming proinflammatory macrophages - Hongyan Lu; Ying Cheng; Xiangling Pu; Xingtao Zhao; Ruolan Li; Ruiqi Sun; Xiaoman Xie; Mingyue Wu; Shuo Zhang; Qiong Pan; Jin Chai (Chemical Engineering Journal, 2025)

Mapping cropland use changes in the Guanzhong Plain of China based on a two-level classification framework - Wei Zhang; Jianhong Liu; Ruolan Jia; Xi Wang; Xiya Yan; Ziqi Wang; Jing Wang; Wei Li; Peijun Sun (International Journal of Remote Sensing, 2025)

Identification and Removal of Light Pollution in Maritime Night-Time Images Based on Spatial Frequency Blocks - Hui Sun; Jingyang Wang; Mingyang Pan; Zongying Liu; Shaoxi Li; Ruolan Zhang; Yang Wei (Journal of Marine Science and Engineering, 2025)
The safety of ships during nighttime navigation has always been a major concern. With the widespread application of technologies such as intelligent recognition, intelligent detection, and unmanned ship navigation at night, nighttime maritime light pollution has significantly affected the effectiveness of these intelligent technologies and navigation safety. Therefore, effectively eliminating nighttime maritime light pollution has become an urgent challenge that needs to be addressed. This paper presents a model based on spatial frequency blocks (SFBs) to solve the problem of light pollution in nighttime sea images. The model includes ResNet-50, an encoder, a decoder, and a discriminator. To enable the model to better remove the influence of light pollution, this study designs a method of first detecting the light pollution area and then removing it. It extracts image information from the space–frequency domain to help eliminate light pollution and retain more image information. The experimental results show that on the nighttime light pollution dataset, the Peak Signal-to-Noise Ratio (PSNR) of the model is improved to 24.91 compared to the current state-of-the-art image restoration model, while the Frechet inception distance (FID) is reduced to 64.85. At the same time, in the real night environment, the model can better remove light pollution to recover the original nighttime information. It has excellent performance and provides a certain reference value for advancing the safety of nighttime maritime navigation.

Correlation analysis and modeling application from objective indicators to subjective evaluation of scented tea: A case study of rose tea - Ruolan Song; Meng Shen; Yanran Wang; Youyi Sun; Jiamu Ma; Qingyue Deng; Xueyang Ren; Xianxian Li; Yuan Zheng; Yingyu He; Feng Zhang; Mingxia Li; et al. (Food Chemistry, 2025)

Injectable exosome-loaded quaternized chitosan/oxidized sodium alginate hydrogel with self-healing, bioadhesive, and antibacterial properties for treating combined radiation-wound injury - Guanqun Peng; Jia Hu; Jinnan Guo; Jiahui Dong; Yuanyuan Zhao; Tong Ye; Fengjun Xiao; Zhiyun Meng; Hui Gan; Ruolan Gu; Peng Han; Wenzhong Sun; et al. (Chemical Engineering Journal, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

Interaction of high amylose corn starch with polyphenols: Modulating the stability of polyphenols with different structure against thermal processing - Haoran Fan; Xu Yao; Zhijun Chen; Ruolan Ma; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Chemistry, 2024)

Semi-dynamic spatial–temporal graph neural network for traffic state prediction in waterways - Le Li; Mingyang Pan; Zongying Liu; Hui Sun; Ruolan Zhang (Ocean Engineering, 2024)

Study on the improvement of complexation efficiency and anti-digestibility of phenolic acids based on electrospun starch fibers - Haoran Fan; Xu Yao; Zhijun Chen; Ruolan Ma; Yanhong Bi; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2024)

Combined exposure of beta-cypermethrin and emamectin benzoate interferes with the HPO axis through oxidative stress, causing an imbalance of hormone homeostasis in female rats - Yuxin Li; Xianzhi He; Bin Sun; Nannan Hu; Jiamin Li; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Reproductive Toxicology, 2024)

Rice bran peptide with α-glucosidase inhibition activity: Preparation, evaluation and molecular mechanism - Weiwei Liu; Ruolan Ma; Gengjie Cui; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Journal of Cereal Science, 2024)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Enhanced dandelion phytoremediation of Cd-contaminated soil assisted by tea saponin and plant growth-promoting rhizobacteria - Jie Yu; Ruolan Xie; Jiang Yu; Huan He; Siwei Deng; Senxu Ding; Xiaoshuang Sun; Hameed Hllah (Journal of Soils and Sediments, 2023)

Effects of radon exposure on gut microbiota and its metabolites short-chain fatty acids in mice - Huimeng Liu; Meiyu Wang; Guangrui Chen; Huiyu Zhou; Jiahui Dong; Lei Yang; Tong Li; Zhiyun Meng; Ruolan Gu; Hui Gan; Zhuona Wu; Shuchen Liu; et al. (Toxicology, 2023)

Molecular encapsulation of cinnamaldehyde in V-type starch: The role of solvent and temperature - Qing Gao; Yanan Sun; Ruolan He; Jiabao Zheng; Bin Zhang; Chin Ping Tan; Xiong Fu; Qiang Huang (Food Hydrocolloids, 2023)

Neuroprotective effect of green tea extractives against oxidative stress by enhancing the survival and proliferation of PC12 cells - Zhenlu Cai; Xiaoxuan Hu; Ruolan Tan; Yunran Feng; Meiqi Sun; Ning Ma; Xingxing Li; Li Huang; Jing An; Qian Ge; Haixia Lu (Molecular & Cellular Toxicology, 2019)